Allogenic Achilles-tendon–bone grafts enable more complete restoration of the native direct enthesis structure in the repair of chronic massive rotator cuff tears - Zhao, Fengyuan; Fu, Xinrui; Zhang, Jiahao; Lin, Lin; Mei, Yu; Yin, Yu; Wang, Jianquan; Yan, Hui (Frontiers in Bioengineering and Biotechnology, 2025)
Massive irreparable rotator cuff tears are difficult to restore when the tendon quality is poor, and the tendon retraction prevents complete repair. In such cases, tendon allograft bridging can restore continuity but cannot replicate the native tendon–bone interface. In this study, we evaluated an Achilles-tendon–bone block allograft (BTA) for anatomic tendon–bone interface reconstruction in a rabbit model of chronic massive rotator cuff tear. Thirty-six rabbits underwent bilateral infraspinatus tendon detachment, followed by repair after 3 weeks using direct suture (DS), tendon allograft without bone block (TA), or BTA. At 8 and 16 weeks, we assessed the magnetic-resonance-imaging-based tendon maturation (signal-to-noise quotient (SNQ)), micro-computed-tomography-based bone volume fraction (BV/TV) and histology, immunohistochemistry (COL I, II, X), and biomechanical-testing-based healing. The BTA group showed superior tendon continuity, significantly lower SNQ, and higher BV/TV than the DS and TA groups (p < 0.05) at both timepoints. The histological examination demonstrated denser collagen fibers, greater fibrocartilage formation, and complete bone–bone fusion in BTA. The immunohistochemical assessment revealed higher COL II and COL X expression, indicating advanced fibrocartilage maturation and mineralization. At 16 weeks, the BTA group achieved the highest ultimate load to failure (113.45 ± 14.45 N) and stiffness (19.65 ± 3.41 N/mm) values, exceeding those of the TA and DS groups (p < 0.05). These results indicate that the Achilles-tendon–bone block allograft bridge effectively reconstructs the layered tendon–bone interface, promotes osteointegration and fibrocartilage regeneration, and enhances biomechanical strength, all of which support its potential as a translational option for functional enthesis reconstruction in massive rotator cuff tear repair.